The 2024 European elections in Cyprus and the rise of the YouTuber Fidias Panayiotou, 9 June 2024 - Triga, Vasiliki; Ioannidis, Nikandros (My University, 2025)
The 2024 European Parliament elections in the Republic of Cyprus (RoC), held alongside local government elections, marked an unprecedented ‘super election day’. This complex electoral event occurred just a year and a half after President Nikos Christodoulides’ narrow victory, amidst declining approval and public mistrust in political institutions. This study explores how second-order election dynamics, unique 2024 conditions, and political de-alignment trends shaped voter behaviour. It further examines the challenges faced by established parties and the rise of independent candidate Fidias Panayiotou, whose success underscores the shift in Cypriot politics towards personality-driven, issue-based, and social media-oriented actors over traditional party structures.
Keywords: Party de-alignment; second-order elections; Fidias Panayiotou; social media; EP elections; disillusionment; protest vote; independent candidates